2020
DOI: 10.1080/21663831.2020.1772395
|View full text |Cite
|
Sign up to set email alerts
|

A novel equiaxed eutectic high-entropy alloy with excellent mechanical properties at elevated temperatures

Abstract: Al 1.7 (at. %) eutectic high-entropy alloy (EHEA) consisting of facecentered-cubic (FCC) and C14 Laves phases was produced by powder metallurgy. The EHEA shows an equiaxed morphology that is different from eutectic lamellar structure. Nanometer L1 2 phase (4-5 nm) further precipitates in FCC matrix. The microstructure is highly stable upon annealing at 1000°C for 100 h, which leads to attractive high-temperature strength. The fracture behaviour is observed to be modified by the equiaxed Laves phase, which cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Following this, other types of HEAs consisting of multiple phases were developed [216,217]. One of these types is eutectic high entropy alloys (EHEAs), forming a subset of HEAs as they exhibit biphasic or triphasic microstructure with predominantly lamellar and a few rod eutectics [218]. lead to high creep resistance, microstructural and thermal stability at high temperature and can be used as potential candidates for structural applications [219].…”
Section: Eutectic Concentrated Multicomponent High Entropy Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this, other types of HEAs consisting of multiple phases were developed [216,217]. One of these types is eutectic high entropy alloys (EHEAs), forming a subset of HEAs as they exhibit biphasic or triphasic microstructure with predominantly lamellar and a few rod eutectics [218]. lead to high creep resistance, microstructural and thermal stability at high temperature and can be used as potential candidates for structural applications [219].…”
Section: Eutectic Concentrated Multicomponent High Entropy Alloysmentioning
confidence: 99%
“…Reports are available of producing multiphase eutectic-like microstructure using processes other than the solidification route. Recently, Han et al [218] reported the development of equiaxed Co 25.1 Cr 18.8 Fe 23.3 Ni 22.6 Ta 8.5 Al 1.7 (at%) EHEA consisting of FCC solid solution phase with nanosized L1 2 ordered precipitates and C14 Laves phase by powder metallurgy route phase. These microstructures are shown to be stable for 100 h at a temperature of 1273 K. They have well-balanced mechanical properties such as yield strength (~800 MPa) and tensile ductility (~16%) at a temperature up to 1073 K. Recently, the deformation processing map of AlCoCrFeNi 2.1 EHEA [233], consisting of 100% of eutectics (CoCrFe-rich (fcc) and NiAl-rich phases), has been investigated to identify the regimes of workability.…”
Section: Eutectic Concentrated Multicomponent High Entropy Alloysmentioning
confidence: 99%
“…Similarly, as well as impurity elements, which segregate to the boundaries, weakening them, there are others which will strengthen the boundaries. Design of engineering alloys (DEA) [67][68][69][70][71][72][73][74] has now become an important field of research with tremendous potential not only for improving the elevated temperature properties of metals and alloys but also improving the room temperature properties. He et al [72] noted that although a lot is known about grain boundary strengthening, little attention has been paid to its effect on mechanical properties, and this is an obvious area for more research.…”
Section: Origin Of the Troughs And Intermediate-temperature Embrittle...mentioning
confidence: 99%
“…He et al [72] noted that although a lot is known about grain boundary strengthening, little attention has been paid to its effect on mechanical properties, and this is an obvious area for more research. DEA has been used to develop high-entropy alloys (HEA) composed of multiple principal elements with exceptionally high strength and thermal stability, and the optimum strength for these alloys has been derived theoretically and confirmed experimentally, but these are isolated cases [73,74]. DEA also has been used to optimise room-temperature strength in highentropy nano-polycrystalline alloys having Fe, Al, Ni, Cr, and Cu present [72,74].…”
Section: Origin Of the Troughs And Intermediate-temperature Embrittle...mentioning
confidence: 99%
“…However, these heterogeneous nanostructures may be unstable at elevated temperatures or difficult to fabricate in bulk sizes [14,15] , which limits their industrial application. On the other hand, at a larger (i.e., sub-micron to micron) scale, the structure of the HEAs could also significantly influence their mechanical properties, as in the case of lamellar structures [16] or equiaxed grains [17] . These structures could be controlled by conventional thermal/mechanical treatments, i.e., cold/hot rolling or annealing [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%